Temperature Dependence of SPEV Cell Membranes Permeability for Molecules of Cryoprotectants - Chernobay, N. A.; Kovalenko, I. F.; Koschiy, S. V.; Kovalenko, S. Ye.; Rozanov, L. F. (Problems of Cryobiology and Cryomedicine, 2011)
Using the method of volumometry the permeability coefficients of SPEV cell membranes for molecules of ethylene glycol (EG), 1,2-butane diol (1,2-BD), glycerol, dimethyl sulfoxide (DMSO) and dimethyl formamide (DMFA) at 35, 20 and 5°С have been determined. The activation energy values of transport for molecules of EG, 1,2-BD and DMSO through the plasma membrane in temperature range of 35...5°C are close and approximately three times as higher than the activation energy of glycerol transport. The permeability coefficients at5°Cfor glycerol and 1,2-BD are almost the same, for DMSO and EG are approximately three times as higher, and the permeability coefficient for DMFA is four orders higher. The permeability for DMFA molecules at35°Cis comparable with permeability of molecules of water, and the permeability coefficients for glycerol are one order lower, than the ones for EG, 1,2- BD and DMSO.